Hate Speech in The Comment Section of The X Account of The Minister of The Republic of Indonesia - Cahyani, Bunga Oktafia; Putri, Rachmadila Adelia; Mubarok, Yasir (GERAM (Gerakan Aktif Menulis), 2026)
The X account of the Minister of Energy and Mineral Resources (ESDM) of the Republic of Indonesia is intended to function as a medium of public information and transparency; however, its comment section frequently becomes a space for the dissemination of hate speech. This study aims to identify and describe the forms of hate speech in the comment section of the minister’s X account using Searle’s theory of illocutionary speech acts. This study employed a qualitative descriptive method. The data consisted of 42 hate-speech comments (N = 42) collected from comments posted on the Minister of Energy and Mineral Resources’ X account in response to a post published on September 17, 2025. Data were collected using non-participant observation (SBLC), documentation, and purposive sampling, and were analyzed using linguistic and contextual analysis. The findings reveal four types of illocutionary speech acts: expressive (27 data; 60%), directive (9 data; 20%), assertive (8 data; 18%), and commissive (1 data; 2%), while no declarative speech acts were identified. The dominance of expressive speech acts indicates that hate speech is primarily used by netizens to express anger, disappointment, hostility, and contempt toward public officials rather than to provide rational criticism. From a forensic linguistic perspective, these linguistic patterns demonstrate a tendency toward emotionally driven cyber behavior that may constitute defamation, insults, intimidation, or threats, thereby potentially violating Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions. The study highlights how hate speech on social media functions not only as a form of digital expression but also as a linguistic practice with significant legal implications in public communication.